Colonoscopic Preoperative Localization Using Submucosal Injection of Radiolabelled Colloid - Carolyn Cho; Sanjiv Jain; Mark Pilbeam; Noel Tait; Andrew Thomson (Canadian Journal of Gastroenterology)
Malignant colonic polyps can be removed endoscopically but surgical resection is sometimes required. However, the polypectomy site can be difficult to locate. Current methods use various tattooing agents, with varying degrees of success. A new technique using pre-operative injection of technetium-99m-labelled antimony colloid, with intraoperative localization using a handheld gamma probe, is described. Although unsuccessful in terms of localizing a previously partially resected polyp, the technique itself proved safe and simple, and has some advantages over other endoscopic approaches.